Political Representation in Representative Democratic Systems: A Study of Crises and the Future - Mawlud, Emad Ahmed; Rasul, Abid Khalid (Journal of Legal and Political Studies, 2023)
Political representation under representative democratic systems suffers from a problem resulting from the representative policy pursued by political elites towards citizens who formed these elites within the framework of practicing their political rights through political participation in elections, which has become the most prominent means of distinguishing democratic systems from others. The policy based on the monopoly of power,the spread of corruption,the marginalization of citizens’rights, subordination to supranational institutions and international interest groups in light of advanced representative democratic systems. This polices have plunged political representation and representative democracy into crises whose features are evident in the decline in the rate of political participation of citizens in elections, and the decline in the rate of political representation and representative democracy. Support and membership of competing political parties, Loss of confidence and credibility among citizens’ political elites. This situation produced a double phenomenon on the political scene: On the one hand, it created intense enthusiasm among some citizens for political participation through support for populist movements and protests outside the official parties and institutions and against the existing political elites. On the other hand, it led to the spread of the phenomenon of political indifference among some other citizens towards what is happening in society under democratic systems. The charade. At the same time, the existing political elite (both right and left orientation ) does not pay any attention to the calls and proposals that have emerged to transcend the reality of political representation and the existing representative democratic systems and have discussed the future of political representation.
Keywords: Political Representation; Representative Democratic; Political Elites; Citizens; Political Participation